2019
DOI: 10.1111/bcpt.13365
|View full text |Cite
|
Sign up to set email alerts
|

Severe poisoning with naproxen causing coagulopathy

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are well known for their most frequent side effects (digestive, renal and metabolic disorders) but are lesser known for other effects, such as coagulation disturbances. In this issue, we report the case of a 58-year-old woman who ingested 26 g of naproxen in a suicidal attempt and developed cardiovascular shock, hypocoagulability and thrombopenia. Her outcome was positive (extubation 3 days after admission [D3], correction of haemostatic disruptions on D5 and of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Schwaiger et al 15 observed hyaline droplet degeneration of tubular epithelial cells and the occurrence of an interstitial nephritis of the fish kidney when exposed to diclofenac. Lelièvre et al 16 reported the development of cardiovascular shock, hypocoagulability and thrombopenia in a case of a 58-year-old woman who ingested 26 g of naproxen in a suicidal attempt. Walsh et al 17 showed the increased prevalence of abomasal ulceration in Holstein calves when treated with IBF (10-day course).…”
Section: Introductionmentioning
confidence: 99%
“…Schwaiger et al 15 observed hyaline droplet degeneration of tubular epithelial cells and the occurrence of an interstitial nephritis of the fish kidney when exposed to diclofenac. Lelièvre et al 16 reported the development of cardiovascular shock, hypocoagulability and thrombopenia in a case of a 58-year-old woman who ingested 26 g of naproxen in a suicidal attempt. Walsh et al 17 showed the increased prevalence of abomasal ulceration in Holstein calves when treated with IBF (10-day course).…”
Section: Introductionmentioning
confidence: 99%
“…copper-dependent protein stress. Many copper ion carriers are widely used as antitumor drugs, such as quinolin-8-ol, flavonoids, and carbamate(20)(21)(22). Hence, cuproptosis might be a breakthrough strategy for cancer therapy.…”
mentioning
confidence: 99%
“…Sua ação antiinflamatória se deve a mecanismo semelhante ao do naproxeno isoladamente, ou seja, supressão rápida e duradoura (24h) da atividade da COX, com consequente redução da síntese de prostaglandina E2 (PGE2) e tromboxano B2 (TXB2), redução da infiltração leucocitária e da concentração das citocinas inflamatórias, dentre elas, interleucina 6 (IL-6), interleucina 1 beta (IL-1β) e da proteína quimiotática para monócitos 1 (MCP1) (DINGENEN et al, 2019;GLANVILLE et al, 2021). A atuação do ATB-346 sobre a produção de TXB2 pode influenciar a hemostasia, inclusive de forma benéfica na prevenção da formação de trombos, mas isso ainda precisa ser investigado (LELIÈVRE et al, 2019).…”
Section: Atb-346: Possível Efeito Sobre a Formação De Trombosunclassified